The “Booty Call”: A Compromise between Men and Women's Ideal Mating Strategies - JONASON, Peter K. (Institutional Knowledge at Singapore Management University, 2009)
Traditionally, research on romantic and sexual relationships has focused on 1-night stands and monogamous pairs. However, as the result of men and women pursuing their ideal relationship types, various compromise relationships may emerge. One such compromise is explored here: the ‘‘booty call.’’ The results of an act-nomination and frequency study of college students provided an initial definition and exploration of this type of relationship. Booty calls tend to utilize various communication mediums to facilitate sexual contact among friends who, for men, may represent low-investment, attractive sexual partners and, for women, may represent attractive test-mates. The relationship is discussed as a compromise between men’s and women’s ideal mating strategies that allows men greater sexual access and women an ongoing opportunity to evaluate potential long-term mates.